UTILIZING LED USAGE ON FORTIMANAGER DEVICE AS A SOFTWARE MONITORING INDICATOR FOR FORTINET ACCESS POINTS - Alfaujianto, Moh (Universitas Utpadaka Swastika, 2024)
In today's digital era, stable connectivity and fast troubleshooting are crucial to support corporate, academic, and research activities. One important component in network infrastructure is the access point (AP) which functions to provide a wireless connection. With the large number of Access Points (AP) provided by campuses or offices, it is required to be easy to monitor and troubleshoot all Access Point (AP) devices. Fortigate, as a solution provider, offers access point and switch monitoring features using LED Usage. This study aims to explain how access point monitoring can be implemented effectively through the FortiManager device and is important to ensure that network devices are functioning properly. FortiManager devices can monitor switches that are connected with active or inactive status, how many active access points are on each switch are monitored, all of which clients are connected to the network can be monitored. Thus, FortiManager devices are very much needed by administrators and network technical teams to facilitate monitoring and troubleshooting.